Inside the small-scale composting of kitchen and garden wastes: Thermal performance and stratification effect in vertical compost bins - Arrigoni, Juan P. (2018)
Fil: Arrigoni, Juan P. Universidad Nacional de Río Negro. Sede Andina. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural (IRNAD); Argentina.